Development of Discovery-Based Physics Teaching Modules to Improve Critical Thinking Skills - Haslinda Viskaali; Helmi Helmi; Kaharuddin Arafah (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2025)
This study is a development research that aims to describe the feasibility of discovery-based Physics teaching modules, practitioner’s assessment on discovery-based Physics teaching modules, improvement of critical thinking skill tests, and to produce discovery-based Physics teaching modules. The method used to achieve this goal is R&D using a 4D model. The research trial subjects were 34 students of Class X.2 natural sciences (IPA) at State Senior High School (SMAN) 9 Gowa. The research instruments used discovery-based physics teaching module validation sheets, practitioner assessment questionnaires, and critical thinking skills test instruments. Based on the results of data analysis, the conclusions obtained are: 1) The discovery-based Physics teaching module was declared valid and suitable for use with slight revisions; 2) The discovery-based Physics teaching module in terms of practitioner responses is that the Physics subject teacher is in the practical category; 3) The effectiveness of the discovery-based Physics teaching module in terms of students' critical thinking skills obtained average N-Gain percentage value is 56% and was in the effective category. Students experience increased critical thinking skills on indicators of interpretation, analysis, and inference. This can be interpreted as saying that the discovery-based Physics teaching module developed is effective in improving students' critical thinking skills